1979
DOI: 10.1295/polymj.11.15
|View full text |Cite
|
Sign up to set email alerts
|

Poly(alkylene oxide) Ionomers. II. Solution Co- and Terpolymerization of Trioxane for the Preparation of Poly(oxymethylene) Ionomers

Abstract: Solution polymerization of trioxane (TO) with 1, 3-dioxolane (DO) gave copolymers of various comonomer compositions. TO was also copolymerized with ethyl glycidate (EG) and terpolymerized with DO and EG to polymers of low EG content. The copolymers were acetate-endcapped or base-treated to give stable co-and terpolymers. The treatment of EG containing poly(oxymethylene) (POM) copolymers with sodium hydroxide in methanol at elevated temperatures gave POM ionomers. The polymers were characterized by their infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Several modified‐POM samples have been prepared, containing a variety of reactive groups as side chain branches from the main polymer backbone and as terminal groups on the polymer chain 14–20. Wissbrun reported that the POM copolymer of trioxane with epichlorohydrin comonomer reacted with thioglycolate to give modified‐POM with carboxylic derivatives 19.…”
Section: Introductionmentioning
confidence: 99%
“…Several modified‐POM samples have been prepared, containing a variety of reactive groups as side chain branches from the main polymer backbone and as terminal groups on the polymer chain 14–20. Wissbrun reported that the POM copolymer of trioxane with epichlorohydrin comonomer reacted with thioglycolate to give modified‐POM with carboxylic derivatives 19.…”
Section: Introductionmentioning
confidence: 99%
“…The results provide possibilities for further and comprehensive improvements in the compatibility with glass binders and, therefore, the mechanical properties of glass‐fiber‐filled POM. Additionally, several modified POM samples have been prepared containing a variety of reactive groups as side‐chain branches from the main polymer backbone and as terminal groups on the polymer chain 17–23. Wissbrun22 reported that a POM copolymer of TOX with epichlorohydrin as a comonomer reacted with thioglycolate to produce a modified POM with carboxylic derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…9 These monomers have been copolymerized with trioxane 10 and the properties of co-and ter-polymers with 1,3-dioxolane with a relatively low percentage of glycidate incorporated were investigated. 11 These polymers were then hydrolyzed to the corresponding poly( oxymethylene)ionomers and their free acids. The co-and terpolymerizations were accomplished with classical cationic initiators, both in bulk solution 11 and by a process in which the monomers were mixed in the vapor phase.…”
mentioning
confidence: 99%
“…11 These polymers were then hydrolyzed to the corresponding poly( oxymethylene)ionomers and their free acids. The co-and terpolymerizations were accomplished with classical cationic initiators, both in bulk solution 11 and by a process in which the monomers were mixed in the vapor phase. 12 Epoxides which have functional groups directly attached to the epoxide rings have been already known.…”
mentioning
confidence: 99%